Regional employment quality: a centralized mechanism for overcoming poverty? - Barba-Solano, Carlos E.; Pozos-Ponce, Fernando (Papeles de Población, 2021)
In this paper it is analyzed employment structure at three regions in the state of Jalisco, Mexico, with an important rural component. A data comparison is made with major Mexican urban areas, in the late 90’s. The results of this comparison show that employment quality and wage levels are quite precarious elsewhere the major urban areas. This debates the main objective of Programa Oportunidades, as rural population has little possibility of overcoming their severe poverty by means of having an occupation like those available at their location.